Evaluasi Sistem Informasi Akademik Universitas Mercu Buana Yogyakarta Menggunakan UTAUT2 - DAVID HADIANSYAH (LPPM Universitas Mercu Buana Yogyakarta, 2020)
One form of the adoption of the College Information Technology (IT) is Academic Information System (SIA) at the University of Mercu Buana Yogyakarta (UMB Yogyakarta). After a few improvements in 2016 and 2017, Directorat ICT felt need to conduct a SIA evaluation with the intention to know the level of admission of students in the use of SIA in Yogyakarta UMB to be the cornerstone in Next development. One of the suitable models for the evaluation of the user's acceptance of technology is a model developed by Venkatesh et al in 2012 which was named the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). The test equipment used in this research is SPSS for validity testing and realibility testing, as well as SmartPLS for final tests. Based on the results of the analysis, this study has eight conclusions of the ten accepted hypotheses. Further intentions of student behaviour and behaviour in the use of SIA are medium or moderate category. Further intentions of student behaviour and behaviour in the use of SIA are medium or moderate category. Keywords: SIA UMB Yogyakarta; UTAUT2; SPSS; SmartPLS; Validity; Reliability.